Pengaruh Bimbingan Kelompok dengan Peer Group Education terhadap Tingkat Pengetahuan tentang Perilaku Seksual Pranikah Remaja di SMK Bina Informatika Kota Bogor Tahun 2024 - Rosdiana Rosdiana; Rina Afrina; Agus Purnama (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Adolescent sexual behavior can be influenced by exposure to mass media, both print and electronic. One of the efforts to improve adolescents' knowledge about sexual behavior is by providing health education. Peers are also a significant source of information about sex in shaping adolescents' sexual knowledge, attitudes, and behavior. This study aims to determine whether or not there is an effect of Group Guidance with Peer Group Education on the Level of Knowledge about Premarital Sexual Behavior of Adolescents at Smk Bina Informatika Bogor City. This study used a pre-experimental research design of the pre-post part in one group (One-group pre-post test design). The results showed that based on the Marginal Homogeneity Test obtained (Asymp.Sig) 0.000 <0.05, Ha was accepted, meaning that there were differences before and after being given group guidance with peer group techniques about adolescent premarital sexual behavior.